2014
DOI: 10.1179/1362171813y.0000000159
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation comparison of laser and laser–arc hybrid welding of Invar 36 alloy

Abstract: Laser and laser-arc hybrid welding are employed to join Invar 36 alloy. The microstructure, coefficient of thermal expansion (CTE) and mechanical properties of laser weld (LW) and hybrid weld (HW) are analysed and compared. The tensile test shows both LW and HW fractured in the weld metal, but the HW is stronger than the LW. Especially, the yield strength of HW is 362?8 MPa, 16?2% higher than that of LW. Both the CTE and Curie temperature of LW are almost the same with those of base material. The CTE of HW is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The chemical composition of Ni kept constant from the BM to WZ. It suggested that almost no Ni loss occurred during the K-TIG welding, which usually occurred in laser-MIG hybrid welding of Invar36 alloy [13]. Ni content was the key to CTE and Curie temperature of Invar36 alloy [2].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical composition of Ni kept constant from the BM to WZ. It suggested that almost no Ni loss occurred during the K-TIG welding, which usually occurred in laser-MIG hybrid welding of Invar36 alloy [13]. Ni content was the key to CTE and Curie temperature of Invar36 alloy [2].…”
Section: Resultsmentioning
confidence: 99%
“…Laser-MIG welding combines laser welding and MIG welding, which has the advantages of deep penetration, good bridging ability and high welding speed. Li et al [13] carried out laser-MIG hybrid welding of 5-mm-thick Invar36 alloy and the weld had excellent tensile strength. But the CTE of the welds was higher than that of the BM due to the change of Ni content in the weld zone (WZ).…”
Section: Introductionmentioning
confidence: 99%
“…The hybrid laser-plasma welding has high rigidity, high temperature and good direction. Li [23] compared the microstructure, coefficient of thermal expansion, mechanical properties of laser weld and hybrid weld metal based on a welding investigation of Invar 36 alloy.…”
Section: Introductionmentioning
confidence: 99%
“…They investigated the effects of temperature field distribution and its relation to element diffusion and concluded that a full penetration dissimilar weld joint between Invar and steel was obtained using their specified welding parameters. Li et al successfully joined two Invar 36 plates using ER309 filler wire [ 33 ]. They used both laser welding and laser-arc hybrid welding to compare the microstructure, thermal expansion characteristics, and mechanical properties of the weld joints.…”
Section: Introductionmentioning
confidence: 99%